2020
DOI: 10.1016/j.ijrobp.2020.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in Radiation Oncology Post–COVID-19 Pandemic: There Is No Turning Back

Abstract: Purpose We aimed to assess patients’ and physicians’ perspectives on wider implementation of telemedicine in radiation oncology practice, disrupted by the novel coronavirus disease 2019 (COVID-19). Methods Quantitative questionnaires were prepared and distributed between May 27 and June 11, 2020. A 29-question survey targeting patients with cancer was distributed electronically via cancer support organizations. Cross-sectional data from a selected weekday at a radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…While a recently initiated ongoing trial in telephonic follow up in gynaecological cancers will provide structured information in future, this cohort of 1100 patients who were attended through teleconsultations during COVID 19 will allow shaping of follow up clinics in near future even as pandemic evolves. Similar insights into integrating telemedicine into radiation oncology have recently been reported (38).…”
Section: Discussionsupporting
confidence: 69%
“…While a recently initiated ongoing trial in telephonic follow up in gynaecological cancers will provide structured information in future, this cohort of 1100 patients who were attended through teleconsultations during COVID 19 will allow shaping of follow up clinics in near future even as pandemic evolves. Similar insights into integrating telemedicine into radiation oncology have recently been reported (38).…”
Section: Discussionsupporting
confidence: 69%
“…7 , 8 Additionally, compared with our respondents, a similar proportion of physicians reported positive experiences with telemedicine in prior single-institution studies. 9 The high rates of satisfaction are encouraging for the future of telemedicine in radiation oncology as prior studies have indicated that provider preference ultimately drives telemedicine use. 10 …”
Section: Discussionmentioning
confidence: 96%
“…Moreover, a cross-sectional study that evaluated the perceptions of physicians and patients on the application of telemedicine in a radiation oncology practice found that 30.6% of patients and 67% of physicians would appreciate a more frequent use of video-consultations. In addition, the majority of patients (59.9% and 63.4%) and radiation oncologists (61.1% and 63.9%) believed that video consultations would be more useful during radiation therapy or during follow-up [68]. A recent descriptive cross-sectional study comprising cancer patients from a tertiary care comprehensive oncology unit during the COVID-19 pandemic found that the majority of patients (64.1%) who were contacted by a clinical oncology specialist using telemedicine, in particularly voice call had breast carcinoma.…”
Section: Teleoncology Covid-19 and Breast Cancermentioning
confidence: 99%